A systemic functional translation analysis of thematic structure: directing attention to Yoda's linguistic manifestation. Issue 1 (2nd January 2016) - Espindola, Elaine
Abstract : Research in the area of translation studies seems to typically overlook the linguistic nature of film translation, concentrating mainly on issues related to extralingusitic aspects of subtitles leaving certain aspects undiscussed as they neglect the linguist dimension of subtitles. Because language as a modeling system helps in the construal of the meanings in the film environment, direct attention to the language of subtitles seems to be a gap that needs to be filled. In the context of Systemic Functional Translation Studies the present article gives direct attention to the language of both the spoken dialogues and the subtitles of the saga Star Wars (directed by George Lucas) by concentrating research efforts on the study of a selected character: Master Yoda. It does so by observing the role of marked and unmarked Themes in the construal of the character's discourse. The results obtained evidenced the contribution of thematic structure to expounding the representation of Yoda both in the spoken source text as well as in the subtitled target text as a wise and powerful character in the galactic community of Star Wars . Finally, direct attention to the linguistic complexity of subtitles evidenced that the SFL analysis has led to the unveiling of Yoda's particular languaging mediating a distinctive world view.